TRADISI “MAPPASIKARAWA” DALAM PERNIKAHAN ADAT BUGIS (Suatu Kajian Perspektif Hukum Islam) - Muh. Sudirman; Mustaring Mustaring (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2019)
The article describes the Mappasikarāwa Tradition in the marriage of Bugis adat perspectives on Islamic law. From the results of the study with theological, philosophical, socilogical, anthropogical and juridical approaches, it can be understood that mappasikarāwa is a local knowledge of the Bugis community in marriage. This mappasikarāwa tradition has taken root in the procession of the Bugis marriage so that no marriage escapes the mappasikarāwa activities even though the implementation is different. Taradisi mappasikarāwa, by looking at the purpose and meaning of the tekadung in it generally corresponds to the principles of Islamic law, because; 1) Contain benefits and logics, 2) General applies to the community in a place or at least among the majority of the community, 3) It has been valid for a long time, not a new custom that will emerge later, 4) Not contrary to the syara 'argument or contradictory with the general principles of Islamic sharia. But the thing that needs to be revitalized is the malloangeng tradition shortly after the mappasikarawa tradition, where both partners compete to stand and step on each other. The myth contained in it is